„W półsłowa” i „w półdźwięku”… O relacji Zygmunta Krasińskiego i Fryderyka Chopina - Hoffmann-Piotrowska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article presents the relationship between Frédéric Chopin and Zygmunt Krasiński both on the biographical level and in the relationship between the word and the sound that Krasiński often wrote about in his letters. A special expression of the dialogue between poetry and music described by the poet are Chopin’s compositions to the words of poets contemporary to him, which is especially true about the words of the motto from Krasiński’s poem Ostatni (The last poem). It is extraordinary in the context of Chopin’s songs as it is not only a musical illustration, but also a sophisticated interpretation of the text through music. The attempts to present poetic content through musical notation presented in the article lead to the conclusion about Chopin as a conscious recipient of a literary work who, like Krasiński, saw in the symbiosis of word and sound the possibility for expressing internal experience.